Musician Do Nhuan and Opera Composing Career - Lam, Do Thi (International Journal of Humanities and Education Development (IJHED), 2024)
Since the musical play Co Sao by musician Do Nhuan, the first Vietnamese opera, was born in 1965 until now, our country's opera art has gone more than half a century. Although it is not a long journey, not yet a massive opera with many works with the participation of many musicians, Vietnamese opera has made great contributions to the country's music, creating a grandeur, a meaningful voice internationally about a musical genre with a large form that requires high artistic composition techniques and methods; affirming the richness, erudition as well as the development of the compositional style of the team of professional music composers. The contributions of Vietnamese opera composers such as Nhat Lai, Nguyen Dinh Tan, Hoang Viet, and Luu Huu Phuoc are truly worthy of recognition and the first person to mention is musician Do Nhuan. Musician Do Nhuan has made great contributions to opera, which is the merit of pioneering a professional music genre, which requires a high level of composers, performers, and audience. Moreover, it is the merit of the musician who has contributed a larger number of opera works than other musicians (up to now, March 2023): 3 operas (Co Sao, Nguoi tac tuong, Nguyen Trai).